Integration of Social Media in Website Based School Information System - Hidayatulloh, Nur Wachid; Dellia, Prita (Sistemasi: Jurnal Sistem Informasi, 2023)
Information systems and social media are a form of rapid development in the era of society 5.0. Both of these can be used in an agency in disseminating information and can be used as promotional media. One institution that is very closely related to this is an educational institution. An existing educational institution has used social media and a website-based information system. SMK PGRI 1 Bangkalan is one of the vocational schools in Bangkalan Regency which does not yet have a website and social media accounts to disseminate information. A website-based social media integrated information system is one of the recommendations in solving this problem. This study uses the waterfall research model in developing the system. The results of this research are a website-based school information system that is integrated with social media, namely WhatsApp and Instagram. In addition, the website that has been created also meets several quality aspects of ISO 25010, namely functional suitability which gets a percentage of 100% and is declared very good, portability which gets a percentage of 100% and is declared very good, performance efficiency which has an average speed of 1,193 which fall into the very good category, and the usability aspect which gets a percentage of 90% and is declared very feasible.